How to create fantasy art for computer games - Stoneham, Bill 1947- (London A. & C. Black, 2010)
This book is a practical guide on how to create artwork for computer games - a burgeoning area in which thousands of artists are hired each year. The guide mostly focuses on fantasy art but the information it gives on media - both traditional and digital, doodling, light, mass and negative space creatures, game genre, working with models, composition, perspective, character development, interactive environments, and atmosphere is pertinent to all computer art. A gallery of fine art and illustration collections is also included making this book the ideal introduction to the world of producing c
"A Quarto book"--T.p. verso
Keywords: Computer drawing; Computer games -- Design; Computer graphics; Computer art